PERAN REFUGIA SEBAGAI MEDIA KONSERVASI ARTHROPODA DI LAHAN PADI DESA DELIKSUMBER - Wijayanti, Ari; Windriyanti, Wiwin; Rahmadhini, Noni (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2021)
Rice is basic neet for Indonesia people. East Java experienced decrease rice production 2% in 2014, the problem was insect pest. Insecticides are dangerous that replaced use refugia attracting biological agens. Purpose of the research to discover the role of refugia as conservation medium in suppressing pets attacks and increasing the diversity arthropod populations in rice fields. This study uses a direct insect sampling method and uses traps such as sweep nets, yellow traps, pitfall traps and light traps. Identification of insects using an introduction to the study insect and iNaturalist. Analysis of the observational data quantitatively by calculating the species diversity index (H’), evenness index (E), Richness index (R) and dominance index (C) then tabulated using excel. observations indicate the number of insects found on land A (rice with refugia) was 5661 individuals consisting of 12 ordo, 61 family and 94 species. Meanwhile on land B (rice without refugia) was 3,198 individuals consisting of 11 ordo, 43 family and 56 species. Refugia affected the population of biological agens more on land A was 2707 individuals than on land B was 1215 individuals. While the pest population on land A much less as 364 individuals than on land B as 763 individuals. Tabulation from the calculation of the species diversity index as 0.142 and 0.118, the species evenness index as 0.030 and 0.025, the dominance index of 0.0004 and 0.0013 is classified as low, while the species richness index of 10.76 and 6.82 is classified as high.